Clinical findings of median rhomboid glossitis in typhoid fever patients: Temuan klinis median rhomboid glossitis pada pasien demam tifoid - Arista, Erlinda Bella; Cahyono, Luqman Mahadika; Nafsih, Thoharoh Laili; Prihastuti, Christiana Cahyani; Purnomohadi, Sigit (Makassar Dental Journal PDGI Makassar, 2025)
Typhoid fever is an acute infection of the gastrointestinal tract caused by Salmonella typhi. Oral manifestations that can appear include median rhomboid glossitis. This article reports a case of MRG in a patient with typhoid fever. A 40-year-old man with com-plaints of fever, mouth ulcers, nausea, vomiting, abdominal pain, diarrhoea, and blackish faeces. The diagnosis of typhoid fever was confirmed. Oral examination revealed a reddish parallelogram-shaped depapillation lesion in the centre of the tongue, which was sore and surrounded by a white coating that could be scraped off. MRG is an inflammation of the tongue characterised by erythema lesions on the median dorsum of the tongue caused by Candida infection. The finding of MRG oral lesions in this ty-phoid fever case is thought to be influenced by the condition of lymphocytopenia which causes a decrease in patient immunity, increasing the risk of opportunistic Candida infection in the oral cavity. In addition, there are also predisposing factors such as smoking habits and poor oral hygiene conditions. It is concluded that the management of MRG lesions is to provide information and education to patients to maintain oral hygiene, avoid consumption of hot and spicy foods and drinks that aggravate com-plaints on the tongue.